Physiological study of sweda mala w.s.r sweat - Saini, Mukesh; Sharma, Rajesh Kumar; Sharma, Dinesh Chandra (International Research Journal of Ayurveda & Yoga, 2021)
Mala (waste) according to Ayurveda like Prakriti(constitution), Dhatu(body tissues), Dosa and Updhatu; mala’ concept is unique in Ayurveda. Mala (waste) known as Aatmbala by Aacharya bhela, Aacharya Bhavprakash says in mala specially life (jeev) is remaining and Aacharya Yogratnakar says that life depend on mala. During digestion end product form is divided into in sara form (aahararasa) (dhatu poshak ansh) and kittabhag (mala poshak ansh)[4]. The human body is nourished by the elements of air, water and food from the external world, by converting these products in bodily assailable form through the process of digestion. During this process of digestion at macro and micro levels, there are also certain bi-products which are produced in the body as excretory wastes. These products are not useful for the body and hence are regularly disposed off if these products are not excreted on a regular basis they can prove harmful for the body. These elements are completely opposite to those of Dhatus and hence these excretory wastes are known as Mala Malinkaranata Mala there are several different excretory wastes formed during the various stages of digestion out of which the Purisha (feces), Mutra (urine) and Sweda (sweat) are the main excretory wastes. We usually ignore the process of sweating unless it happens in excess and gives bad odor to the body. Today let’s explore how this simple process of sweating influence skin texture, constitution of body to the definite signs of death. Ayurveda mentions different substances that influence normal functioning of the body. Normal excretion of sweda (sweat) is one among them.